Asupan protein dan vitamin e berhubungan dengan kadar hemoglobin Pasien Talasemia di RSU Kabupaten Tangerang - Humaira Difaura Rahman (ARGIPA (Arsip Gizi dan Pangan), 2020)
Thalassemia is a genetic disease that are passed from parents to children through DNA which causes blood cells to lack globin chains. Children with thalassemia experienced an increase in energy expenditure, a lack of vitamin and minerals so that it has an impact on the state of malnutrition which will have a direct effect on the growth of patients with thalassemia. This study’s purpose was to analiyzing relationship between protein intake, iron, vitamin C, vitamin E, and nutrition status with hemoglobin levels in thalassemia patients in the Tangerang Regency Hospital. The subjects of this study are 29 thalassemia patients. The method of the research is cross-sectional. Sampling method of this study was quota sampling and technique of data analysis with Pearson Moment Product. Average protein intake was 96%, average iron intake was 72,5%, average vitamin C intake was 79,5%, average vitamin E intake was 51,1%, average z-score was -1,59 SD and hemogloblin level 8,1 g/dl. The results showed that protein intake and vitamin E intake related to hemoglobin levels. Whereas iron intake, vitamin C, and nutritional status not related to hemoglobin level. Keywords: Hemoglobin Levels, Protein Intake, Thalassemia, Vitamin E